Can non-hormonal therapy be effective in management of menopause symptoms? - Sobstyl, Małgorzata; Tkaczuk-Włach, Joanna; Sobstyl, Jacek; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2013)
Women often use non-hormonal therapy in management of menopause symptoms because safety of hormonal therapies is controversial. Antidepressant agents such as venlafaxine reduce hot flashes. Also gabapentin is effective in reducing hot flashes. Lifestyle changes and exercise can be useful as auxiliary management of vasomotor symptoms. Non-pharmacological therapy such as yoga, relaxation, acupuncture need to be evaluated in large randomized placebo-controlled trials.